Freezing of water within heat storage container with involve of nanoparticles. (July 2022) - Zhang, Jixin; Zhang, Yilin; Alhazmi, Sharifah E.; Rothan, Yahya Ali; Nofal, Taher A.; Musa, Awad
Abstract: In this study, the influence of inclusion of alumina nanoparticles with various size and concentration on treatment of solidification of water has been analyzed. To reach the new properties of working material, formulations based on single phase methodology was utilized and effect of size of particles were incorporated in estimating the conductivity of NEPCM. Galerkin method was implemented for solving the mathematic model which contains two equations with neglecting the buoyancy term. Grid style changes with changing the time stage and such adaptive grid results in more accurate outputs. Validation based on previous benchmark study shows good agreement and it proves the utilized assumptions are reasonable. As nanoparticles add the freezing time declines around 41.14% because of stronger conduction mode. Besides, changing the concentration of alumina from 0.02 to 0.04 makes the rate of freezing to intensify around 19.36%. As diameter of particles intensifies up to 40 nm, the freezing speed augments around 19.93% but augmenting d p from 40 to 50 nm causes the this factor to decline around 49.12%. Highlights: The impact of inclusion of alumina nanoparticles on solidification was studied. Grid style changes with changing the time stage in present simulation. As nanoparticles add the freezing time declines around 41.14%. As dp intensifies up to 40 nm, the needed time declines around 19.93%.